Философско-антропологические аспекты концепции музыкального воспитания в культуре Древней Греции - Казина, Н.В. (Культура народов Причерноморья, 2013)
В статье рассматриваются философско-антропологические аспекты концепции
музыкального воспитания Древней Греции, в частности, учения о музыкальном этосе. Основное
содержание исследования представляет анализ антропологических идей античных философов –
Пифагора, Платона, Аристотеля – в контексте формирования личности средствами музыки. Отмечена
актуальность антропологического потенциала данной концепции для современного общества.
Ключевые слова: музыкальное воспитание, учение об этосе, антропология. У статті розглядаються філолофсько-антропологічні аспекти концепції музичного виховання
Древньої Греції, зокрема, вчення про музичний етос, що трактує музику як засіб етико-виховного впливу
на людину. Основний зміст дослідження становить аналіз антропологічних ідей античних філософів –
Піфагора, Платона, Аристотеля – у контексті формування особистості засобами музики. Відзначено
актуальність антропологічного потенціалу даної концепції для сучасного суспільства.
Ключові слова: музичне виховання, вчення про этос, антропологія. The article examines the philosophical and anthropological aspects of the concept of musical
education ancient Greece, in particular, the doctrine of the musical ethos, treats music as a means of ethical and
educational impact on people. The main content of this research is the analysis of the anthropological ideas of
ancient philosophers in the context of identity formation by means of music. Musical ethos is the character of the
impact of music on people depending on its emotional component. The ancient Greeks believed that music is an
imitation of the human characters.
Musical concepts of Pythagoras, Plato, Aristotle, is an important phase in the development of ethics, practice
and theory of education. For the development of musicology and philosophy of music all determine important
role in study of ancient music. Is marked the relevance of the anthropological potential of this concept for a
modern society. Thus, the study of music in the socio-cultural and anthropological aspect makes it possible to
comprehend and to harmonize the processes of art and culture, taking place in society, as a universal means of
socialization, formation of the inner world, which is based on the value priorities laid the spiritual and moral
development.
Keywords: music education, the doctrine of ethos, anthropology.